Gaya Kepemimpinan Kepala Sekolah dan Motivasi Guru Persfektif Psikologi Pendidikan - Sukatin Sukatin; Muammar Qadafi; Vira Yuniar; Nadia Milatillah; M. Sanul; Aqil Arya Yolanda; M. Akbar Risqi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study is motivated by the importance of the school principal's leadership style in enhancing teacher work motivation a key factor in the successful delivery of education. The study aims to analyze the relationship between the principal's leadership style and teacher motivation from the perspective of educational psychology. A qualitative approach was employed using a literature review method, involving the search, selection, analysis, and synthesis of relevant scholarly sources, including journal articles, books, and academic documents. Data analysis was conducted using content analysis to identify key themes regarding principal leadership styles and teacher motivation. The findings indicate that democratic, transformational, and situational leadership styles positively influence teacher work motivation through effective communication, the provision of rewards, teacher involvement in decision-making, and support for competency development. From an educational psychology perspective, principal leadership plays a role in fulfilling teachers' psychological needs such as a sense of appreciation, self-confidence, and opportunities for growth thereby enhancing commitment, professionalism, and the quality of instruction. The study implies that adopting an adaptive leadership style that is attuned to teachers' psychological aspects can foster a conducive school environment and support the continuous improvement of educational quality.